Alterations of the human skin microbiome after ocean water exposure. (August 2019) - Nielsen, Marisa Chattman; Jiang, Sunny C.
Abstract: Skin is the body's first line of defense against invading microorganisms. The skin microbiome has been shown to provide immunity against exogenous bacterial colonization. Recreational water exposures may alter the skin microbiome and potentially induce skin infections. This study explored the link between ocean water exposures and the human skin microbiome. Skin microbiome samples were collected, using swabs, from human participants' calves before and after they swam in the ocean, and at 6 hour and 24 hour post-swim. Genomic analysis showed that skin microbiomes were different among individuals before swimming. But after swimming, microbial communities were no longer different, which was demonstrated by a decrease in inter-sample diversity. Taxonomic analysis showed that ocean bacteria, including potential pathogens, replaced the native skin bacteria and remained on the skin for at least 24 hour post-swim. This research provides insight into the relationship between the human skin microbiome and the environment. Graphical abstract: Unlabelled Image Highlights: Skin exposure to ocean water results in the deposition of new bacteria on the skin. Ocean water washes off normal resident bacteria from human skin. Some bacteria acquired from the ocean can cause human infection. Microbial community alterations persist for at least 24 hour post-exposure